State of the art - optimization techniques in cloud environment - Priya, B; Gnanasekaran, T (International Journal of Engineering and Technology, 2018)
A Cloud is a network of a shared pool of configurable and computing resources providing efficient, on-demand pay-as-per-use access. Its main objectives being: Scalability, High availability of resources and to reduce the overhead incurred. Scheduling is the method of determining the order by which the jobs have to be executed. It determines the various tasks that are to be executed in parallel and the efficient resource to carry out the tasks. Load balancing is the method of balancing the load across various resources by fixing a threshold and migrating the tasks to the under loaded resources based on the threshold. Optimization techniques are used to find a finite solution for scheduling of tasks although not optimal. Various optimization techniques are employed based on Cost, CPU utilization and to balance the load. This paper deals with the importance of optimization, the various metrics and constraints associated. A literature survey on the various optimization techniques is also analyzed based on the attributes of the tasks.Â Â